2014
DOI: 10.3892/etm.2014.1703
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differentially expressed genes in cold-exposed mice to investigate the potential causes of cold-induced hypertension

Abstract: Cold exposure is considered to be an important contributing factor to the high morbidity of hypertension. In order to elucidate the cause and mechanism of cold-induced hypertension (CIH), gene expression analysis was performed on microarray data for two groups of cold-exposed mice (4°C for 1 week and 4°C for 5 weeks, three replicates per group) and their respective control groups maintained at 30°C. Analysis results indicated that the differentially expressed genes with the most significance were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Cold exposure was also found to increase the frequency of heart rate variability and ventricular ectopic beats 22. In addition, exposure to cold caused significant increase of inflammatory cytokines and methane dicarboxylic aldehyde and decline of superoxide dismutase (SOD) and glutathione peroxidase activity,23 and the genes involved in the hypoxia-inducible factor signalling pathway were activated in which oxidative stress-associated genes were significantly upregulated, including SOD2 and epoxide hydrolase 2 24. On the other hand, exposure to hot weather may induce profound physiological changes, such as increase in blood viscosity and cardiac output leading to dehydration, hypotension, surface blood circulation increase and even endothelial cell damage 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold exposure was also found to increase the frequency of heart rate variability and ventricular ectopic beats 22. In addition, exposure to cold caused significant increase of inflammatory cytokines and methane dicarboxylic aldehyde and decline of superoxide dismutase (SOD) and glutathione peroxidase activity,23 and the genes involved in the hypoxia-inducible factor signalling pathway were activated in which oxidative stress-associated genes were significantly upregulated, including SOD2 and epoxide hydrolase 2 24. On the other hand, exposure to hot weather may induce profound physiological changes, such as increase in blood viscosity and cardiac output leading to dehydration, hypotension, surface blood circulation increase and even endothelial cell damage 25.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the attributable fraction was calculated assuming the causality between cold/hot temperatures and mortality, although the evidence is still limited on this association. However, extensive epidemiological studies have shown that the cold and hot temperatures have impacts on human mortality2 3 8–11 and morbidity 24 30. Fourth, the use of data on temperatures were from fixed monitoring sites rather than measuring individual exposure, which may create to some extent measurement errors in the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that cold exposure for weeks increased blood pressure in mice [ 16 , 23 , 24 ]; however, whether a short-term cold exposure leads to hypertension in hours remains unclear. In the current study, exposure of wild-type mice to a 7° C environment unexpectedly increased the blood pressure of mice within 1 h (Figure 1A experiment outline, 1B, and 1C).…”
Section: Resultsmentioning
confidence: 99%
“…30 Gene expression analysis in cold-exposed mice indicated that differentially expressed genes were associated with adaptive thermogenesis, fatty acid metabolism and energy metabolism. 31 Genes involved in the hypoxia-inducible factor-1 signalling pathway were activated, genes associated with oxidative stress (such as superoxide dismutase 2, mitochondrial and epoxide hydrolase 2, cytoplasmic) were significantly upregulated, whereas genes involved in inflammation-associated pathways were shown to be downregulated in a 4℃ 5-week group. 31…”
Section: Discussionmentioning
confidence: 96%
“…31 Genes involved in the hypoxia-inducible factor-1 signalling pathway were activated, genes associated with oxidative stress (such as superoxide dismutase 2, mitochondrial and epoxide hydrolase 2, cytoplasmic) were significantly upregulated, whereas genes involved in inflammation-associated pathways were shown to be downregulated in a 4℃ 5-week group. 31…”
Section: Discussionmentioning
confidence: 96%